2014
DOI: 10.4194/1303-2712-v14_2_18
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The present study was designed to evaluate the use of Spirulina, Arthrospir platensis as a protein source for hybrid red tilapia fries (Oreochromis niloticus x Oreochromis mossambicus) with average weights of 206±11 mg. Spirulina was incorporated into diets at 0, 50, 75, and 100% of the fishmeal-based diet. The test diets were fed to the fish at 12% body weight three times a day for consecutive 65 days at 24±2°C. The final weight gain, specific growth rate, feed conversion ratio (FCR) and survival rate of fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…In contrast to the results of research Ungsethaphand et al (2010) found that the fish fed supplemented with different concentrations of S. platensis not provide a significant difference in the survival rates of fish. Feeding S. platensis of hybrid red tilapia (O. niloticus x O. mossambicus) also did not provide a significant difference in all treatment groups compared with the control (El-Sheekh, El-Shourbagy, Salaby, & Hosny, 2014). On the contrary, Jana et al (2014) recorded that feeding Spirulina to fish improved survival rates, the highest obtained in fishes fed with 5% Spirulina.…”
Section: Hematological Gurami Feed With Experimental Dietsmentioning
confidence: 91%
“…In contrast to the results of research Ungsethaphand et al (2010) found that the fish fed supplemented with different concentrations of S. platensis not provide a significant difference in the survival rates of fish. Feeding S. platensis of hybrid red tilapia (O. niloticus x O. mossambicus) also did not provide a significant difference in all treatment groups compared with the control (El-Sheekh, El-Shourbagy, Salaby, & Hosny, 2014). On the contrary, Jana et al (2014) recorded that feeding Spirulina to fish improved survival rates, the highest obtained in fishes fed with 5% Spirulina.…”
Section: Hematological Gurami Feed With Experimental Dietsmentioning
confidence: 91%
“…From our literature search, not many literatures focused on the antibacterial mechanism of Spirulina specifically, as most reports generally explained the antibacterial mechanism of microalgae. Katircioglu et al (2005) stated that the antimicrobial activity of microalgae can be elucidated by the presence of cyclic peptides, lipopolysaccharides and alkaloids, the activity maybe as a result of toxins produced by microalgae cells since some blue green algae are known to produce toxins with potent pharmaceutical uses (El-Sheekh et al, 2014). Alves et al (2013) submitted in their study on the mechanism of anti-MRSA that only phenolic acids (benzoic and cinnamic acid derivatives) were the main compounds with anti-MRSA activity at a point in their research, illustrating the relevance of the carboxylic group in the molecular structure (proton recipient).…”
Section: Spirulina As An Antibacterialmentioning
confidence: 99%
“…Moreover, more recent works have equally supported the above observations on the incorporation of Spirulina into fish diets. El-Sheekh et al (2014) who studied the effect of Arthrospira platensis on the growth and carcass of hybrid red Tilapia observed and recommended that 75% Spirulina can conveniently substitute fishmeal-based diet with increased feed conversion ratio as well as protein value in proximate composition of the carcass. A 10% replacement of fishmeal with Spirulina in the feeding trial of common carp (Cyprinus carpio) gave significantly higher body weight as against other treatments and the control (Abdulrahman et al, 2014), on the other hand Ibrahem et al (2013) observed improved feed conversion ratio and growth rates in striped jack and Tilapia (Pseudocaranx dentex and Oreochromis niloticus).…”
Section: Applications Of Spirulina In Aquaculturementioning
confidence: 99%
“…Arthrospira platensis Gomont 1892 is the most applicable algae throughout the recent decades due to the fact that in terms of the chemical composition it is a very rich food source of both macro-and micronutrients including high-quality protein content up to 70% of the dry weight, essential fats (e.g., gamma-linolenic and oleic acids), essential amino acids, vitamins (e.g., B12), β-carotene, lipids and polysaccharides with a distinctive high content of calcium, iron, phosphorous, minerals, sulfated and phycocyanin, besides its antioxidant capacity (Phang et al, 2000;Babadzhanov et al, 2004;Abdel-Daim et al, 2015, 2020Mofeed, 2019). Moreover, A. platensis showed neither chronic nor any acute toxicity or even harmful effects, making it safe to use as part of diets for human food and as a dietary supplement of poultry and fish feed production as a non-conventional high protein source (Habib et al, 2008;El-Sheekh et al, 2014). Arthrospira platensis as many microalgae can be cultivated in both closed and open systems to get a commercial value.…”
Section: Introductionmentioning
confidence: 99%